Rural Electrification and Microenterprises Performance: Some Lessons from Muranga County Kenya - Kariuki, Daniel; Kimuyu, Prof.; Nyangena, Dr. (International Journal of Economics, 2016)
Purpose: The purpose of this study was to assess rural electrification adoption by microenterprises in Muranga County Kenya. The study was guided by two specific objectives which are; to establish the determinants of rural electrification adoption by Micro and Small enterprises in Murang'a County, Kenya and to determine the effect of adoption of rural electrification on the performance of rural micro and small enterprises in Murang'a County, Kenya. Methodology: This study adopted two stage least squares incase of violation of endogeneity. The population of this research consists of the 650 small and medium enterprises in Murang'a. The study used primary data. Results: Results revealed that, amount of capital invested, nature of business activity and distance from market significantly influenced the predicted probability of electricity adoption. Results also revealed that electricity adoption was positive and significantly related with business performance. The results also indicated that gender, capital invested and workforce were positively and significantly related to business performance. Unique contribution to theory, practice and policy: It is recommended that Murang'a County should conduct business incubation programmes for businesses so as to boost the business performance/turnover as well as the capital invested. This will have a positive effect on electricity adoption since well performing businesses are likely to adopt electricity.